2022
DOI: 10.1096/fj.202101608r
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differences in N6‐methyladenosine RNA methylomes in the rat adenohypophysis after GnRH treatment

Abstract: N6-methyladenosine is considered to be the most common and abundant internal chemical modification among the more than 150 identified chemical RNA modifications. It is involved in most biological processes and actively participates in the regulation of animal reproduction. However, the potential function of m 6 A in the pituitaries of mammals is not yet clear. It is also unknown whether m 6 A is involved in the secretion and regulation of FSH by GnRH, which in turn affects mammalian reproduction. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…GnRH is involved in the regulation of the entire hypothalamic–pituitary–gonadal axis and plays an important role in reproductive regulation [ 44 ]. Our previous research revealed significant differences in methylation levels in the adenohypophyses of rats after GnRH treatment [ 24 ]. In addition, 14 circRNAs were found to be significantly differentially expressed in the rat adenohypophysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GnRH is involved in the regulation of the entire hypothalamic–pituitary–gonadal axis and plays an important role in reproductive regulation [ 44 ]. Our previous research revealed significant differences in methylation levels in the adenohypophyses of rats after GnRH treatment [ 24 ]. In addition, 14 circRNAs were found to be significantly differentially expressed in the rat adenohypophysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rat is a common experimental animal model for research on the effect of GnRH on the pituitary gland. Various studies have used rat experimental animal models to explore the expression changes of gonadotropins in the adenohypophysis after a GnRH treatment [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired steroid production and release in D. melanogaster prothoracic glands leads to developmental delay and precocity [ 46 ]. In mammals, the potential role of m6A modification in the regulation of reproductive hormone secretion was found to be linked with steroid biosynthetic processes [ 47 ]. On the other hand, the mobilization of energy is tightly coupled to a variety of metabolic pathways, in which the fat body coordinates insect growth with metamorphosis or reproduction by storing or releasing key elements associated with these events [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenohypophysis tissue and blood were collected 10 min after the second treatment for subsequent experiments. The specific protocol was described in detail in our previous research [ 32 , 50 ].…”
Section: Methodsmentioning
confidence: 99%